PHYTOCHEMISTRY AND PHARMACOLOGICAL ACTIVITIES OF ARAGVADH (CASSIA FISTULA LINN): A REVIEW - Ramesh Chandra, Tewari; Suresh, Chaubey; Gagan Deep, Kour; Naveen, Kumar (International Journal of Ayurveda and Pharma Research, 2015)
Aragvadh (Cassia Fistula Linn) also known as Purging Cassia or Indian Laburnum is an important medicinal plant used in Indian system of medicine The Purging Cassia also called Cassia fistula Linn. is a moderate to medium sized deciduous tree which is very common in Indian continent. The fruit pulp contains the anthraquinone and rhein(I) in the free state as well as in the form of glycoside, responsible for significant mild purgative action. The oldest record of its medicinal use can be traced as far as 3000 years when Charak and Sushruta used Aragvadh in the treatment of different kinds of skin diseases (Kushthas). The present article gives an account of updated information on this important plant which is highly beneficial for different ailments. The review reveals about different activities of plant like purgative, diuretic, laxative, anti-asthmatic, hepato protective, anti-allergic and various other important medicinal properties. This will also provide valuable information which will assist the scientists in getting more advanced knowledge about this plant species.